Чеська мова сьогодні й завтра. Доповідь Ольги Мартінцової «Неологічні тенденції в сучасній чеській мові» - Мацурова, Я. (Лексикографічний бюлетень, 2011)
The contribution recapitulates a presentation Neological Tendencies in Modern Czech language delivered by Ph.D. Olga Martincová at Charles University, Prague on December 1st, 2011. The prominent Czech scientist presented her understanding of terms «neologism», «neological tendency» and outlined the most distinct tendencies in modern Czech language.